Philanthropy in Education: What’s the Cost? - Waterman, Nick (Advances in Social Sciences Research Journal, 2018)
The hollowing-out of the state has rendered countries more susceptible to influences of external policy actors. Neo-liberal strategies of the New Public Management and the New Policy Agenda emphasise the importance of alternative service providers to the state. A resultant “contract culture” facilitates not only gap-filling in service delivery, but also penetration of policy spaces by non-state actors. Globalisation has also served to diminish the state and facilitate external policy actors. This paper adopts a critical perspective on the potential impacts of philanthropic support for education on public policy. Individual and corporate philanthropy challenge public policy-making autonomy, especially in developing countries. Involvement in public policy-making and dissemination and implementation of policy through transnational policy networks further contribute to erosion of the sovereignty of the state. Influence on public policy can occur either through coercion or voluntarism on a push-pull basis, whereby philanthropy may push recipients into policy conformity through selective and policy-based funding, or pull recipients to formulate polices that are compatible with individual and corporate policy agendas.